Interaction of childhood abuse and depressive symptoms on cortical thickness: a general population study - Voss, Sara; Frenzel, Stefan; Klinger-König, Johanna; Janowitz, Deborah; Wittfeld, Katharina; Bülow, Robin; Völzke, Henry; Grabe, Hans J. (European archives of psychiatry and clinical neuroscience, 2022)
Childhood abuse was inconsistently related to whole-brain cortical thickness in former studies. However, both childhood abuse and cortical thickness have been associated with depressive symptoms. We hypothesised that childhood abuse moderates the association between depressive symptoms and cortical thickness. In 1551 individuals of the general population, associations between whole-brain cortical thickness and the interaction of childhood abuse (emotional, physical, and sexual) and depressive symptoms were analysed using an ANCOVA. Linear regression analyses were used to estimate the same effect on the cortical thickness of 34 separate regions (Desikan-Killiany-atlas). A significant interaction effect of childhood abuse and depressive symptoms was observed for whole-brain cortical thickness ( F (2, 1534) = 5.28, p = 0.007). A thinner cortex was associated with depressive symptoms in abused ( t value = 2.78, p = 0.025) but not in non-abused participants ( t value = − 1.50, p = 0.224). Focussing on non-depressed participants, a thicker whole-brain cortex was found in abused compared to non-abused participants ( t value = − 2.79, p = 0.025). Similar interaction effects were observed in 12 out of 34 cortical regions. Our results suggest that childhood abuse is associated with reduced cortical thickness in subjects with depressive symptoms. In abused subjects without depressive symptoms, larger cortical thickness might act compensatory and thus reflect resilience against depressive symptoms.